Identidad nacional e intervención extranjera. Nicaragua, 1840-1930 - Kinloch Tijerino, Frances (2002)
The autor highlights the complexity of relations between local actor and the agents of foreing powers ; their modes of cooperation, submission, and resistance under diverse social contexts; and resistance under diverse social contexts; and the unexpected or paradoxical results of foreign interventions in the construction of the national idea of Nicaragua.